5(x+2)-(5x+10)=0

Simple and best practice solution for 5(x+2)-(5x+10)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)-(5x+10)=0 equation:


Simplifying
5(x + 2) + -1(5x + 10) = 0

Reorder the terms:
5(2 + x) + -1(5x + 10) = 0
(2 * 5 + x * 5) + -1(5x + 10) = 0
(10 + 5x) + -1(5x + 10) = 0

Reorder the terms:
10 + 5x + -1(10 + 5x) = 0
10 + 5x + (10 * -1 + 5x * -1) = 0
10 + 5x + (-10 + -5x) = 0

Reorder the terms:
10 + -10 + 5x + -5x = 0

Combine like terms: 10 + -10 = 0
0 + 5x + -5x = 0
5x + -5x = 0

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4x+2=10x-1 | | 80*6x=45+32*4x+23x | | (3x+1)(2x-4)-x(6x-7)=0 | | 32=48t+16t^2 | | .25(16x-20)=.5(10x-8) | | 6y-2x=24 | | 5t+5=-2-7t | | 5y-2y=21 | | 15x^2+2x-56=0 | | 4p+5q= | | 8d=-4+12 | | 16(x-64)=32 | | 5k+6=15 | | x^6-12x^4+48x^2-60=0 | | 53x+56/26-69*(85*4)=5 | | 5+2b=10-3b | | 7x+8=64 | | 98-7x=11x+24 | | 12-5*(5-4x)=27 | | 115-6x=30x+23 | | 4p-3=7 | | 6y+3x=24 | | 54-4x=5x+20 | | 8x-3=2c+15 | | x(3x+11)=4 | | 14-10x=142-38x | | 7-7x=207-42x | | 6x+9=-135-10x | | 144-5x=6x-9 | | -19-3x=5-9x | | 15x+2=13x-8 | | 5n-11=2n+4 |

Equations solver categories